Design of a Biocatalytic Filter for the Degradation of Diclofenac and Its Ozonation Products - Schmiemann, Dorothee; Schneider, Jessica; Remek, Marcel; Kaulertz, Jeremy; Seifert, Oliver; Weidmann, Monika; Opwis, Klaus; Cordes, Arno; Jäger, Martin; Gutmann, Jochen Stefan; Hoffmann‐Jacobsen, Kerstin (Engineering in life sciences, 2025)
ABSTRACT Posttreatment of the effluents from wastewater treatment plants is becoming increasingly important, as the conventional treatment cannot completely remove organic trace contaminants. Promising techniques like chemical oxidation methods, including ozonation, face the challenge of potentially generating more toxic transformation products than their parent substances due to incomplete oxidation. In this work, the laccase from Trametes versicolor was immobilized on a polyester textile to create a biocatalytic textile filter for the posttreatment of organic trace contaminants and their ozonation by‐products. Different filter designs for reactive filtration with biocatalytic textiles were implemented on the laboratory scale and tested for their effectiveness in degrading the dye Remazol Brilliant Blue, the pharmaceutical diclofenac, and its ozonation products. The plate module, inspired by lamellar clarifiers and featuring the textile with covalently immobilized enzyme on the lamella surfaces, exhibited the best performance characteristics. Employing this module, a continuous process of diclofenac ozonation and subsequent posttreatment with the biocatalytic filter was conducted. This not only demonstrated the feasibility of continuous biocatalytic wastewater filtration but also highlighted improved degradation efficiencies of ozonation products compared to the batch process using laccase in solution.